Efektifitas Perguliran Modal Penguatan dan Pengembangan Usaha Ekonomi Produktif Program Pemberdayaan Ekonomi Masyarakat (PEM) di Kota Kupang - Charles Kapioru (Jurnal Inovasi Kebijakan, 2019)
The City Government of Kupang has launched a Community Economic Empowerment Program (PEM) since 2013, aiming to strengthen and develop the creative economy of small-scale community, through the revolving of venture capital without interest of Rp. 90,320,150,000 to 15,395 participants with the arrears value of the refund amounting to Rp. 6.2 billion (6.86%). This study aims to determine the effectiveness of the revolving PEM program funds on improving business performance and income of program participants, as well as finding recommendations for strategies to solve the problem of funds being rolled out. This policy evaluation research method uses secondary data sourced from in-depth interviews with relevant stakeholders, previous research study reports, and other data summarized from online public information sources. The results showed that the performance of business management is still simple and can be proven by the reason of choosing the type of business is still based on the wishes of the participants, the condition of the business location is not all feasible, business operations have not been managed properly, financial administration without bookkeeping, an increase in sales turnover only occurs in the type and certain business scale, also there has been no increase in business scale and business diversification. Irregularities in revolving funds occur because business management is not yet business oriented, and there is a lack of mentoring activities in human development, business development, and institutional development. The handling of PEM funds bottlenecks can be pursued through social sanctions, and the application of both civil and criminal law as a last resort to ensnare participants who are not in good faith. The right to claim can be handed over to the Lurah, LPM and Prosecutor in his capacity as Regional Head, Assistant and State Lawyer